Evaluation of the Pancasila Ideology Development Policy for Educators at the Pancasila Ideology Development Agency - Miduh Sanches Marihot; Ermaya Suradinata; Layla Kurniawati (Sean Institute, 2025)
The problem in the implementation of training is that the objectives of the training program have not been achieved, such as increasing the competence of training participants, this is evidenced by the results of the pretest and posttest scores which are not too different. Therefore, an evaluation is needed in the implementation of the PIP training program. Considering that there has never been an evaluation of the PIP training program for the 2023 and 2024 budget years, especially in the implementation of education and training for PIP training teachers. The importance of program evaluation includes providing information that is used as a basis for making policies and decisions. The objectives of this study are, 1) to evaluate the training program for PIP training teachers at BPIP in the 2023 and 2024 fiscal years, 2) to analyze the obstacles and barriers to evaluating the training program for PIP training teachers at BPIP in the 2023 and 2024 budget years, 3) to analyze the efforts of the training program for PIP training teachers at BPIP. This research method uses a naturalistic qualitative approach (case study). By using the CIPP evaluation model. The evaluation components are: 1) context, 2) input, 3) process and, 4) product. The data analysis technique used is the Miles and Huberman model. The results of the study on the context dimension did not find any gaps, the input dimension still found gaps in the indicators: 1) facilities and infrastructure, 2) methods, and 3) teaching materials, the process dimension still found gaps in the training implementation indicators, and the product dimension still found gaps in the accreditation indicators.